Reversed Phase Paper Chromatographic Separation of Lead(II) and Bismuth(III) - K. Uphade, Bhagwat; R. Aher, Haribhau.; R. Kuchekar, Shasikant (Asian Journal of Chemistry, 2010)
Reversed phase paper chromatographic separation of lead and bismuth have been carried out on Whatman no.1 filter paper impregnated with n-octylaniline as a stationary phase and using organic complexing agents such as sodium acetate, sodium malonate, sodium succinate, sodium citrate and sodium salicylate solutions as a mobile phase. Various experiments were carried out to study the effect of pH (4.0, 7.0 and 9.0), concentration range of mobile phase (0.01-0.1 M) and concentration of stationary phase (0.1-0.5 % using chloroform as a diluent) on the Rf values of individual cations Optium concentration of n-octylaniline, mobile phase and pH were determined. The proposed method is applicable for separation and detection of lead and bismuth in various samples.